2019
DOI: 10.1002/solr.201900077
|View full text |Cite
|
Sign up to set email alerts
|

An Operando Study on the Photostability of Nonfullerene Organic Solar Cells

Abstract: Nonfullerene organic solar cells (OSCs) have achieved an impressive power conversion efficiency (PCE) over the past few years, showing a great potential for real applications. However, the study on the photostability and degradation mechanism of nonfullerene OSCs is far behind than that of fullerene‐based solar cells, which is crucial for the commercial applications of the technology. Herein, an efficient and stable nonfullerene OSC based on PCE10:rhodanine‐benzothiadiazole‐coupled indacenodithiophene with bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 51 publications
0
62
0
1
Order By: Relevance
“…Most of the stability studies so far have been focused on fullerene‐based OSCs, [ 7–10 ] while for unstable NFA‐based OSCs, understanding of the degradation mechanism is still limited. For NFA‐based systems, promising photostability has been demonstrated for many‐systems including P3HT:IDTBR, [ 11 ] PCE10 with EH‐IDTBR, [ 12 ] or IEICO‐4F, [ 13 ] PffBT4T‐2OD:EH‐IDTBR, [ 14 ] single‐component devices [ 15 ] as well as ITIC derivatives. [ 4,16 ] However, studies up to date indicated that the light stability of NFA systems is strongly materials‐dependent.…”
Section: Figurementioning
confidence: 99%
“…Most of the stability studies so far have been focused on fullerene‐based OSCs, [ 7–10 ] while for unstable NFA‐based OSCs, understanding of the degradation mechanism is still limited. For NFA‐based systems, promising photostability has been demonstrated for many‐systems including P3HT:IDTBR, [ 11 ] PCE10 with EH‐IDTBR, [ 12 ] or IEICO‐4F, [ 13 ] PffBT4T‐2OD:EH‐IDTBR, [ 14 ] single‐component devices [ 15 ] as well as ITIC derivatives. [ 4,16 ] However, studies up to date indicated that the light stability of NFA systems is strongly materials‐dependent.…”
Section: Figurementioning
confidence: 99%
“…For photostability testing, the devices were encapsulated with a glass cover in a glove box maintained under a dry N 2 atmosphere to exclude possible photochemical degradation effects caused by the presence of oxygen and moisture. Light exposure was performed using a LED source with an illumination wavelength that ranged from 380 to 1000 nm and an illumination equivalent of 1 sun [19]. The luminescent spectrum of the LED is presented in Fig.…”
Section: Device Measurement and Characterizationmentioning
confidence: 99%
“…Given this importance, more and more studies have attempted to address the photostability issues associated with NFA-based OSCs, with major efforts focused on identifying donor/acceptor systems that display enhanced morphological stability [16][17][18]. As part of these efforts, we have reported recently that donor/acceptor pairs with good miscibility can achieve stable morphologies with enhanced photostability, and allow for OSC operating lifetimes (T 80 ) of over 2000 h [19]. Similarly, in a recent study, Du and coworkers [13] reported an efficient OSC based on a PBDB-T donor and an ITIC-2F acceptor with a PCE of 8% and a T 80 lifetime of 11,000 h. These values represent one of the best reported stability results for OSCs in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] On the one hand, the stability related to the microstructure of a bulkheterojunction (BHJ) photoactive layer is essential for long-term stability; on the other hand, the stability of interface materials and the compatibility between the photoactive layer and the interface layer play a key role in determining efficiency and stability of OSCs. [16][17][18][19][20] By tuning the properties of the photoactive layer, such as tailoring the chemical structure of both donor (D) and acceptor (A), or incorporating a "phase compatibilizer" or "molecular lock" between D/A components, the microstructure stability of BHJ photoactive layer could be addressed. [21][22][23][24][25] However, interface-associated device's instability is less frequently investigated and analyzed for state-of-the-art OSCs.…”
mentioning
confidence: 99%